Charles S. Hamlin papers - Hamlin, Charles S. (Charles Sumner), 1861-1938.; Hamlin, Anna, -1925.; Hamlin, Huybertie Pruyn, 1873-1964.; Robles, Sebastian T. (Sebastian Tomas), 1902-1959.
Correspondence, diaries, speeches, writings, biographical notes, scrapbooks, newspaper clippings, printed matter, and other papers relating chiefly to Hamlin's service in the U.S. Dept. of the Treasury and the Federal Reserve System; Hamlin's civic affairs; and his family's social life in Washington, D.C. Topics include leaders and policies of the Democratic Party especially during the Grover Cleveland, Woodrow Wilson, and Franklin D. Roosevelt administrations and Hamlin's law practice in Boston, Mass. Includes copies of Huybertie Pruyn Hamlin's manuscript pertaining to the Hamlin, Pruyn, and Roosevelt families and to social visits (November 1941-January 1942) to the White House where guests included Winston Churchill and other prominent leaders; diaries and scrapbooks of the Hamlin's daughter, Anna Hamlin; and genealogical information concerning the Hamlin family. Of special interest is an original cartoon depicting Hamlin drawn by Sebastian T. Robles for the Washington Post.
Correspondents include Newton Diehl Baker, John H. Clarke, Frances Folsom Cleveland, Grover Cleveland, Josephus Daniels, Edith Benham Helm, Herbert Hoover, Cordell Hull, Robert Lansing, Henry Cabot Lodge, William Gibbs McAdoo, William McKinley, Levi P. Morton, Richard Olney, George Foster Peabody, Franklin D. Roosevelt, Theodore Roosevelt, William H. Taft, and Woodrow Wilson.
Diaries, index-digests of diaries, and indexes to scrapbooks available on microfilm
Scrapbooks available only on microfilm
Microfilm produced from originals in the Manuscript Division.
Lawyer, U.S. assistant secretary of the treasury, and member of the Board of Governors of the Federal Reserve System. Full name: Charles Sumner Hamlin.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Churchill, Winston, -- 1874-1965.; Clarke, John H. -- 1857-1945 -- Correspondence; Cleveland, Frances Folsom, -- 1864-1947 -- Correspondence; Cleveland, Grover, -- 1837-1908.; Cleveland, Grover, -- 1837-1908 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Helm, Edith Benham, -- 1874-1962 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Morton, Levi P. -- 1824-1920 -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Hamlin family; Pruyn family; Roosevelt family; United States. -- Department of the Treasury; Board of Governors of the Federal Reserve System (U.S.); Democratic Party (U.S.); Finance, Public -- United States; Practice of law -- Massachusetts -- Boston; United States -- Politics and government -- 1865-1900.; United States -- Politics and government -- 1901-1953.; Washington (D.C.) -- Social life and customs; Lawyers; Public officials